G-protein coupled receptor, signal and signal-transduction related transcript mapping in nigral volume and pigmented neurons reveals a potential deficit of nigral feedback signals associated with Parkinson’s disease - John M. Haynes (PLoS ONE, 2026)
Microarray and Next Generation Sequencing studies offer insight into gene regulation in Parkinson’s disease (PD). However, analysing vast numbers of genes can make the interpretation of data difficult when considering the platforms and techniques used across different studies. In this study, transcript expression, restricted to genes related to G-protein coupled receptors, activating agonists, agonist precursors, synthesis enzymes and transduction processes, as well as stress-related chaperones and solute carriers, was assessed across nine microarray platforms and two RNAseq studies of the substantia nigra (nigral volume). Changes in gene expression associated with PD were assessed by differential expression analysis while RNAseq studies were also used to calculate transcript per million values for each of the genes within the nigral volume. This analysis showed extensive changes in nigral volume signalling for several robustly expressed signal-related transcripts including tyrosine hydroxylase ( TH ), WNT signalling components ( SFRP1 , RSPO2 and DKK3 ), Kallikrein Related Peptidase 6 ( KLK6 ), neurexins ( NRXN1 , NRXN3 ), prostaglandin synthases ( PTGES2 , PTGES3 ) and fractalkine ( CX3CL1 ). The nigral volume signalling ligand data was then cross-referenced to the most abundant G-protein coupled receptor and signal transduction transcripts in the pigmented neurons using two RNAseq and two microarray studies. There were 32 significant changes in G-protein coupled receptor and associated signalling genes in pigmented neurons from PD tissue. Of these, 30 genes were upregulated. Analysis of the transcription factors likely regulating the 30 upregulated genes indicates a stimulation of cell stress pathways, particularly the JNK-MAP kinase pathway. Following this pathway back to changes in nigral signalling transcripts indicates that deficits in at least two autocrine/paracrine signalling systems; dopamine, via Gα o -coupled dopamine D 2 receptors and Dickkopf-3 (DKK3) appear likely to contribute to pigmented neuron stress in PD.